Chemical and Ecological Studies on Tilapia Nilotica - Mohamed, A.E.; Awadallah, R.M.; Gabr, S.A. (Asian Journal of Chemistry, 2010)
Atomic absorption spectrophotometry was utilized for the determination of Ag,Au,Ca,Cr,Cu,Fe,K,Mg,Mn,Na,Ni,Pb,Sr and Zn in 42 Tilapia nilotica fish samples collected from river Nile at Aswan (15 samples from the place between the conservation area of Awada and Gebel Tagoug, and 27 samples from the main stream, 15 from the latter samples were placed in the middle of Kima drain draft and the remainder in the river Nile just beyond the end of Kima drain draft contact with Nile). Average length ranges from 13 to 26 cm, weight ranges from 98–400 gm, and water content equals 74.37–75.40%. The results show that trace element concentrations are clearly consistent with size of fish species (length and weight), particularly, relatively large size fish contain higher concentrations of Na,Mn,K,Cu,Cr,Sr and Zn. Also, contaminated Kima drain draft water may not reflect any change in concentrations of the metals in fish. The trace element concentrations in the investigated fish samples are below the safety baseline levels. Statistical relative errors equal 4.8–8.5% and standard deviation ═ 0.0263–303.557.